DESCRIPTION OF NITRATE CONTAMINATION IN SUPERFICIAL AND UNDERGROUND WATERS OF POLTAVA REGION - Фесенко, О. Г. (Scientific Progress & Innovations, 2014)
The process of contamination of nature environment by nitrates, in particular, superficial water resources is researched. Growing of chemicalization in agriculture, foremost applications of high doses of mineral fertilizers, strengthen tension in biological circulation of matters, increase a contamination of agrolandscapes hazard. It is discovered on the basis of analytically statistical research, that one of major pollutants of environment, in particular, water in the Poltava area, there are nitrates. The results of researches of superficial water are on maintenance of nitrates from data of the Poltava regional state project-technological center of guard of fertility of soils and quality of products.